2002
DOI: 10.1037/0097-7403.28.4.388
|View full text |Cite
|
Sign up to set email alerts
|

Acquired equivalence and distinctiveness of cues: II. Neural manipulations and their implications.

Abstract: Neural manipulations were used to examine the mechanisms that underlie the acquired equivalence and distinctiveness of cues in rats. Control rats and those with excitotoxic lesions of either the hippocampus (HPC) or entorhinal cortex (EC) acquired the following conditional discrimination: In Contexts A and B, Stimulus X-->food and Stimulus Y-->no food, and in Contexts C and D, Y-->food and X-->no food. Rats then received many food pellets in A but not in C. After this treatment, control rats showed more magazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 45 publications
7
76
2
Order By: Relevance
“…It is, however, unlikely that the EC serves as a simple relay for the transmission of information from the sensory thalamus and parahippocampal cortices to the hippocampus (Kerr et al, 2007). Indeed, an increasing number of studies indicate distinct roles of the EC and of the hippocampus proper in information processing (Coutureau et al, 1999(Coutureau et al, , 2002Shohamy et al, 2000;Talnov et al, 2003;Sargolini et al, 2006). Moreover, no persistent activity bridging the long time gap between the CS and US has so far been recorded in the hippocampus proper during trace fear conditioning (Gilmartin and McEchron, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, unlikely that the EC serves as a simple relay for the transmission of information from the sensory thalamus and parahippocampal cortices to the hippocampus (Kerr et al, 2007). Indeed, an increasing number of studies indicate distinct roles of the EC and of the hippocampus proper in information processing (Coutureau et al, 1999(Coutureau et al, , 2002Shohamy et al, 2000;Talnov et al, 2003;Sargolini et al, 2006). Moreover, no persistent activity bridging the long time gap between the CS and US has so far been recorded in the hippocampus proper during trace fear conditioning (Gilmartin and McEchron, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The application of this theory in explaining the role of the hippocampus in forming configural memory of non-spatial cues has been challenged on several grounds (e.g. [53]). Furthermore, until recently, there were relatively few tests that sought to determine whether the formation of a configural memory for the spatial and temporal properties of cues is reliant upon the hippocampus.…”
Section: Configural Memory For What Where and Whenmentioning
confidence: 99%
“…In addition, the results of Group DR versus Group DE in Experiment 2 suggested that shared associations with a US may provide the basis for increases in generalization among otherwise distinctive CSs. Conversely, in studies of "acquired distinctiveness," generalization between similar CSs has been attenuated by pairing them with different outcomes (Coutureau et al, 2002;Delamater, 1998;Honey & Hall, 1989Honey & Ward-Robinson, 2002). For example, Delamater (1998) conducted training in which two auditory stimuli (A1, A2) and two visual stimuli (V1, V2) were each paired with one of two types of food outcome (labeled here as ϩ or #).…”
Section: Methodsmentioning
confidence: 99%